Getting work done : prioritize your work, be more efficient, take control of your time, - Harvard Business School (20 minute manager series, 2014)
Demands on your time are growing by the hour, and work keeps piling up. Unclear goals, constant interuptions, and urgent tasks are competing for your attention; you know that your're working less effectively than you could be. This boos will organized at work so you can be more productive by showing you how to: - Prioritize you tasks. - Create to-do lists that work. - Organize your physical and virtual workspace. - Develop a daily routine and stick to it. - Stay forcused and stop procrastinating. - Work more efficiently with others. - Asscess your progress